Impact of the COVID-19 pandemic on oral health and psychosocial factors - Ciardo, Antonio; Simon, Marlinde M.; Sonnenschein, Sarah K.; Büsch, Christopher; Kim, Ti-Sun (Scientific reports, 2022)
The objective of this study was to investigate oral health-related quality of life (OHRQoL) in times of the COVID-19 pandemic and to examine a possible association to psychosocial factors like psychological stress and symptoms of depression and anxiety disorders. Secondary research questions were whether people changed oral hygiene regimens during the COVID-19 pandemic and to what extent dental symptoms existed and developed compared to pre-pandemic. For this cross-sectional study a survey has been conceptualized to determine OHRQoL, stress, depression and anxiety and their specific confounders in a German cohort. Validated questionnaires as OHIP-G14, PHQ-Stress and PHQ-4 have been implemented. Altogether 1178 participants completed the survey between May and August 2020. The overall OHIP-G14 sum score of 4.8 +/- 7.5 indicated good OHRQoL. 21% of the participants (n = 248) reported toothache, 23% (n = 270) mucosal problems, 31% (n = 356) hypersensitivity of the teeth and 27% (n = 305) myofacial pain. The PHQ-Stress score (4.5 +/- 3.5) demonstrated a mild severity of stress. Depression and anxiety level has been mild to moderate (PHQ-4 score: 2.4 +/- 2.6). 38% of the participants stated subjectively greater emotional burden compared to pre-pandemic. Statistically significant differences exist for OHRQoL, stress, anxiety and depression levels between participants with greater, equal or less emotional burden compared to pre-pandemic. COVID-19 history and aggravated levels of depression, anxiety, and stress seem to associate with lower OHRQoL. Psychosocial consequences during pandemic times and their association to oral health should be further investigated.
Gesehen am 13.04.2022